The investigation of K‐shell fluorescence parameters of Zn–Fe alloys with different grain size and microstrain values. (14th March 2017) - Kup Aylikci, N.; Sampaio, J.M.; Kahoul, A.; Aylikci, V.; Karahan, I.H.; Guerra, M.; Santos, J.P.; Marques, J.P.; Tiraşoğlu, E.
Abstract : It is known that zinc alloys with iron group metals have better corrosion resistance than pure zinc. Owing to the corrosion resistance of these alloys, Zn–Fe coatings are widely used in automotive industry and have excellent mechanical performance. In this work, we investigated the relationship between the changes in the measured X‐ray fluorescence parameters ( K β / K α, σ Kα and σ Kβ ) and the changes in the structural parameters such as microstrain or grain size values for Zn–Fe alloys that were prepared with different pH values. To explain these changes, the K α and K β X‐ray production cross sections, and the K β / K α X‐ray intensity ratio values were calculated by three different ways for the elemental forms of Zn and Fe. The structural parameters, such as microstrain and grain size, were also calculated. We expect that the outer shell electronic distribution affects the structural parameters of the produced Zn–Fe alloys, changing the measured K α and K β X‐ray production cross sections, and the K β / K α X‐ray intensity ratio values. We also show that Zn–Fe alloy mi nimum microstrain value corresponds to the maximum changes in K β X‐ray production cross‐section values of Fe and Zn. Copyright © 2017 John Wiley & Sons, Ltd.